Poor prognostic factors for relapse of interstitial lung disease with anti-aminoacyl-tRNA synthetase antibodies after combination therapy - Matsuda, Shogo; Kotani, Takuya; Oe, Katsumasa; Okazaki, Ayana; Kiboshi, Takao; Suzuka, Takayasu; Wada, Yumiko; Shoda, Takeshi; Takeuchi, Tohru (Frontiers in Immunology, 2024)
Introduction This study aimed to identify useful clinical indicators for predicting the relapse of interstitial lung disease (ILD) complicated with anti-aminoacyl-tRNA synthetase (ARS) antibodies (anti-ARS-ILD), being treated with prednisolone and calcineurin inhibitors. Methods Fifty patients with anti-ARS-ILD were enrolled between October 2014 and August 2022. All patients were treated with prednisolone and calcineurin inhibitors as remission induction therapy and followed up for over a year with these combination therapies. We examined patients who experienced ILD relapse after immunosuppressive treatment. We explored the risk factors for predicting ILD relapse in these patients by comparing demographic, clinical, laboratory, and radiological findings and treatments between the relapsed and non-relapsed groups on admission. Results Of the 50 patients, 19 (38%) relapsed during a median follow-up of 4.8 years. Univariate and multivariate Cox regression analyses identified the presence of acute/subacute (A/S)-ILD, higher serum aldolase (ALD) and surfactant protein-D (SP-D) levels, and lower %forced vital capacity (FVC) as risk factors for relapse in patients with anti-ARS-ILD. Using the receiver operating curve analysis, ALD ≥6.3 U/L, SP-D ≥207 ng/mL, and %FVC ≤76.8% were determined as the cut-off levels for indicating a poor prognosis. The 5-year relapse rate was significantly higher in patients with A/S-ILD, serum ALD≥6.3 U/L, serum SP-D ≥207 ng/mL, or %FVC of ≤76.8% than in those without these parameters. (P=0.009, 0.0005, 0.0007, 0.0004, respectively) Serum ALD levels were significantly correlated with the disease activity indicators of anti-ARS-ILD. Conclusion The presence of A/S-ILD, higher serum ALD and SP-D levels, and lower %FVC are useful indicators for predicting anti-ARS-ILD relapse.